Yield and water productivity variation of Boro rice with irrigation strategies and transplanting dates under climate change – a case study in south-western Bangladesh - Tapos Kumar Acharjee; Mohammad Abdul Mojid; Kamonashish Haldar (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
Climate change has imposed major uncertainties on food and water security in Bangladesh. Understanding the recent changes in potential yield and water productivity of major crops is essential to formulate effective adaptation strategies under climate change conditions. This study assessed the yield and water productivity variation of dry season Boro rice with different irrigation regimes and transplanting dates over long-term (1985-2017) in a south-western District (Khulna) of Bangladesh using AquaCrop model. The evaluation of yield and water productivity was done for five transplanting dates (1st & 15th of December and January and 1st of February) and four irrigation strategies (fixed short- and long-interval irrigations, and measured irrigation with ‘low stress, low dose’ and ‘high stress, high dose’). Transplanting rice seedlings on 1st December results in 17% yield increase compared to transplanting on 1st January. There are significant (p£0.05) increasing trends of attainable biomass, grain yield and water productivity of Boro rice. The measured irrigation practices are superior to the traditional fixed irrigation practices. The ‘low stress, low dose’ irrigation strategy increases irrigation-water productivity and provides an opportunity to exploit the possible benefits of climate change. Adjustment of the irrigation strategy can reduce water usage without reducing the potential yield of Boro rice with an eventual increase in irrigation-water productivity, while adjustment of the transplanting date can increase potential yield with additional water usage. These findings would help develop suitable agricultural adaptation strategies for irrigated rice cultivation under climate change.